Illustrated State‐of‐the‐Art Capsules of the ISTH 2021 Congress. Issue 5 (16th July 2021) - Krishnaswamy, Sriram; Ageno, Walter; Arabi, Yaseen; Barbui, Tiziano; Cannegieter, Suzanne; Carrier, Marc; Cleuren, Audrey C.; Collins, Peter; Panicot‐Dubois, Laurence; Freedman, Jane E.; Freson, Kathleen; Hogg, Philip; et al.
Abstract: This year's Congress of the International Society of Thrombosis and Haemostasis (ISTH) was hosted virtually from Philadelphia July 17–21, 2021. The conference, now held annually, highlighted cutting‐edge advances in basic, population and clinical sciences of relevance to the Society. Despite being held virtually, the 2021 congress was of the same scope and quality as an annual meeting held in person. An added feature of the program is that talks streamed at the designated times will then be available on‐line for asynchronous viewing. The program included 77 State of the Art (SOA) talks, thematically grouped in 28 sessions, given by internationally recognized leaders in the field. The SOA speakers were invited to prepare brief illustrated reviews of their talks that were peer reviewed and are included in this article. The topics, across the main scientific themes of the congress, include Arterial Thromboembolism, Coagulation and Natural Anticoagulants, COVID‐19 and Coagulation, Diagnostics and Omics, Fibrinogen, Fibrinolysis and Proteolysis, Hemophilia and Rare Bleeding Disorders, Hemostasis in Cancer, Inflammation and Immunity, Pediatrics, Platelet Disorders, von Willebrand Disease and Thrombotic Angiopathies, Platelets and Megakaryocytes, Vascular Biology, Venous Thromboembolism and Women's Health. These illustrated capsules highlight the major scientific advances with potential to impact clinical practice. Readers are invited to take advantage of the excellent educational resource provided by these illustrated capsules. They are also encouraged to use the image in social media to draw attention to the high quality and impact of the science presented at the congress.